INTEGRATION OF AUGMENTED REALITY IN FIQH LEARNING: Improving The Competence of Technological Pedagogical Content Knowledge (TPACK) Of Madrasah Teachers - Fathurohim, Fathurohim; Muliyah, Pipit; Nasrulloh, Nasrulloh (Jurnal Asy-Syukriyyah, 2024)
This study explores the use of Participatory Action Research (PAR) to integrate Augmented Reality (AR) in teaching Fiqh, specifically the Hajj material, at Madrasah Ibtidaiyah in Sidareja District. Involving 20 teachers, the research followed the PAR cycle, consisting of planning, action, observation, and reflection. The implementation of AR, supported by the Technological Pedagogical Content Knowledge (TPACK) framework, helped teachers effectively incorporate technology in the classroom, enhancing their teaching practices. It also made learning more engaging and accessible for students, improving their understanding of the Hajj material. The results show that AR can significantly improve students' comprehension of Fiqh and support interactive, technology-enhanced learning in religious education.